Acute renal failure in cirrhotic patients with severe sepsis: Value of urinary interleukin‐18. Issue 1 (19th December 2012) - Tsai, Ming‐Hung; Chen, Yung‐Chang; Yang, Chih‐Wei; Jenq, Chang‐Chi; Fang, Ji‐Tseng; Lien, Jau‐Min; Hung, Cheng‐Chieh; Weng, Hsu‐Huei; Wu, Cheng‐Shyong; Peng, Yun‐Shing; Shen, Chien‐Heng; Tung, Shui‐Yi; et al.
Abstract Background and Aim Acute renal failure (ARF) is a common complication of liver cirrhosis and severe sepsis. Differentiating functional renal failure from acute tubular necrosis (ATN) has been difficult in this clinical setting. It has been shown that urinary interleukin 18 (IL‐18) can serve as a sensitive marker for ARF and ATN. This study was aimed to investigate the diagnostic and prognostic values of urinary IL‐18 in ARF associated with liver cirrhosis and severe sepsis. Methods We prospectively evaluated the relationship between urinary IL‐18 and clinical outcomes in 168 consecutive cirrhotic patients with severe sepsis. Results One hundred and eight patients (64.3%) developed ARF at admission to the intensive care unit. ARF was associated with higher urinary IL‐18 and impaired effective arterial volume. Renal failure was functional in 64 (59.2%), due to acute tubular necrosis (ATN) in 30 (27.7%), and mixed type in 14 (12.9%). Patients with ATN had significantly higher levels of urinary IL‐18, rates of vasopressor dependency, and hospital mortality than those with functional renal failure. By using the areas under receiver operating characteristic (AUROC) curve, urinary IL‐18 demonstrated an excellent discriminative power (AUROC 0.882) for diagnosing tubular injury in those with ARF. Meanwhile, hospital survivors had significantly lower urinary and serum IL‐18 levels, compared to non‐survivors. In multivariate analysis, urinary IL‐18, international normalized ratio, and mean arterial pressure were independent factors to predict hospital mortality. Conclusions Urinary IL‐18 can serve as a diagnostic and prognostic marker in cirrhotic patients with severe sepsis.